(untitled) (Zaporizhzhia Historical Review, 2021)
In article a features of becoming and the general contents of the soviet methodology of a history, its connection with the ideology, which dominated in the USSR, and with the marxist theory of formations, the reasons and character of crisis of both a marxist paradigm, and the specified methodology are analyzed. The author comes to the conclusion that the theory of formations has some inherent flaws: logic discrepancy, a teleologic orientation, materialistic ambiguities, scientific inconsistency. It testifies its ontologic and epistemologic imperfection and self-insufficiency.